Importance of Surveillance of Antimicrobial Resistance with its Challenges: Bangladesh Perspective (Bangladesh Journal of Infectious Diseases, 2023)
Abstract not availableBangladesh Journal of Infectious Diseases, June 2022;9(1):1-2